A Child Stunting Against Acute Respiratory Infections in Developing Countries: A Scoping Review - Fadhila, Akbar Kholish; Rahfiludin, Mohammad Zen; Suyatno, Suyatno (Journal of Maternal and Child Health, 2024)
Background: Acute Respiratory Infections (ARIs) are a leading cause of morbidity and mortality among young children, particularly those who experience stunting. This study aims to map the factors associated with ARIs in stunted toddlers using a scoping review methodology. Subjects and Method: This scoping review was conducted using data obtained from PubMed Central. The target population included toddlers with stunting and ARIs. A search was performed using the keywords "stunting AND acute respiratory infections AND toddler," yielding 712 articles, which were narrowed down to 8 relevant articles after applying a 10-year time frame. The factors influencing ARIs in stunted toddlers were categorized into five groups: (1) environmental and sanitation factors, (2) nutritional factors, (3) socio-economic factors, (4) co-infections, and (5) genetic and biological factors.       Results: The factors influencing ARIs in stunted toddlers were categorized into five groups: (1) environmental and sanitation factors, (2) nutritional factors, (3) socio- economic factors, (4) co-infections, and (5) genetic and biological factors. ARIs and stunting are interrelated through various complex factors. Conclusion: A multidisciplinary approach is essential to enhance access to healthcare services, improve nutritional education, and address sanitation conditions, with the goal of reducing the prevalence of ARIs and stunting in toddlers, thereby supporting optimal growth.